Dissecting the Metal Selectivity of MerR Monovalent Metal Ion Sensors in Salmonella - Ibáñez, María Marta (2013)
Two homologous transcription factors, CueR and GolS, that belong to the MerR metalloregulatory family are responsible for Salmonella Cu and Au sensing and resistance, respectively. They share similarities not only in their sequences, but also in their target transcription binding sites. While CueR responds similarly to Au, Ag, or Cu to induce the expression of its target genes, GolS shows higher activation by Au than by Ag or Cu. We showed that the ability of GolS to distinguish Au from Cu resides in the metal-binding loop motif. Here, we identify the amino acids within the motif that determine in vivo metal selectivity. We show that residues at positions 113 and 118 within the metal-binding loop are the main contributors to metal selectivity. The presence of a Pro residue at position 113 favors the detection of Cu, while the presence of Pro at position 118 disfavors it. Our results highlight the molecular bases that allow these regulators to coordinate the correct metal ion directing the response to a particular metal injury.